2013
DOI: 10.1097/sla.0b013e31827b6bbc
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Perioperative Glycemic Control in General Surgery

Abstract: Objective To determine the relationship of perioperative hyperglycemia and insulin administration on outcomes in elective colon/rectal and bariatric operations. Background There is limited evidence to characterize the impact of perioperative hyperglycemia and insulin on adverse outcomes in patients, with and without diabetes, undergoing general surgical procedures. Methods The Surgical Care and Outcomes Assessment Program is a Washington State quality improvement benchmarking-based initiative. We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 489 publications
(136 citation statements)
references
References 49 publications
3
127
2
4
Order By: Relevance
“…reported that every 40 mg/dL increase from normoglycemia (<110 mg/dL) led to a 30% increased risk of infection. Kwon et al 13. also found a clear dose–response relationship between BG and SSI in favor of a lower BG level.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whmentioning
confidence: 89%
See 4 more Smart Citations
“…reported that every 40 mg/dL increase from normoglycemia (<110 mg/dL) led to a 30% increased risk of infection. Kwon et al 13. also found a clear dose–response relationship between BG and SSI in favor of a lower BG level.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whmentioning
confidence: 89%
“…Although non‐DM patients had a lower incidence and decreased severity of hyperglycemia compared with DM patients, hyperglycemia was also associated with adverse outcomes in non‐DM patients 13, 16, 17. In the assessment of operative‐day BG in non‐DM patients who underwent colectomy, normoglycemia (≤120 mg/dL) endured in 26.2%, whereas 53.6% had BG of 121–160 mg/dL, 15.1% had 161–200 mg/dL, and 4.5% >200 mg/dL 18.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whmentioning
confidence: 99%
See 3 more Smart Citations